Law beyond Israel from the Bible to the Qur'an - Zellentin, Holger Michael 1976- (Oxford Oxford University Press, Incorporated, 2022)
The Hebrew Bible formulates two sets of law: one for Israelites and one for gentiles living in the Holy Land. Law Beyond Israel argues that the laws for non-Israelites form the historical basis of qur'anic law, pointing to legal continuity from the Hebrew Bible to the New Testament and from late antique Christianity to nascent Islam.
Description based on publisher supplied metadata and other sources
Keywords: Gentiles (Jewish law); Islamic Law; Electronic books